2013
DOI: 10.1007/s00270-013-0576-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Embolization With Spherical Embolic Agent for Pulmonary Metastases From Renal Cell Carcinoma

Abstract: TAE with SAP-MS might be a well-tolerated and locally efficacious palliative option for patients with pulmonary metastases from RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…found that three sessions of BACE with SAP‐MS lowered the ECOG‐PS score from 3 to 0 in a patient with a large lung cystic adenocarcinoma . Furthermore, several studies have confirmed that BACE with SAP‐MS did not increase the rate of SAEs . BACE combined with SAP‐MS or DEB was therefore associated with a better performance status.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…found that three sessions of BACE with SAP‐MS lowered the ECOG‐PS score from 3 to 0 in a patient with a large lung cystic adenocarcinoma . Furthermore, several studies have confirmed that BACE with SAP‐MS did not increase the rate of SAEs . BACE combined with SAP‐MS or DEB was therefore associated with a better performance status.…”
Section: Discussionmentioning
confidence: 93%
“…Seki et al . found that BACE with SAP‐MS was associated with ORRs of 38.8%, 44.9%, and 38.8% after 1, 3, and 6 months, respectively, in patients with unresectable pulmonary metastases from renal cell carcinoma . Thus, DEB‐BACE is a feasible treatment option for patients with lung cancer refractory to standard treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mean of 2.8 treatments per patient was performed. As seen with RCC mets treated with bland embolization [8], response correlated with degree of iodized oil enhancementpartial response in 35%, stable disease in 26% and progression in 39%.…”
Section: Tpce To Achieve Tumor Regressionmentioning
confidence: 80%
“…Seki et al performed particle embolization of 49 lesions caused by renal cell carcinoma (RCC) (22 pulmonary nodules, 17 mediastinal nodes, and 10 hilar nodes) in 16 patients over 1 to 5 sessions. 8 In these cases, the authors described the use of small particles to achieve a therapeutic, bland embolization. Bronchial arteries were embolized in almost all patients (87.5%) and nonbronchial feeders were included in the majority.…”
Section: Bland Tae To Achieve Tumor Regressionmentioning
confidence: 99%